Historical and juridical considerations about the ‘connections Church-World’ in the Council of Trent and in the Second Vatican Council - NACCI, MATTEO (Prawo Kanoniczne, 2017)
The present work is a conference in the Faculty of Law of the Catholic University of Murcia (Spain) and want to consider the importance of the juridical science named ius publicum ecclesiasticum and the connections between the Church and the Civil Governments. The focus of the study, in my intention, is to underline the important ‘juridical culture’ of this special part of the Canon law.